Preservation of Inner Ear Functions: Extending Glucocorticoid Therapy by Tissue-Protective α1-Antitrypsin - Amit Amar; Eli C. Lewis; Daniel M. Kaplan; Sabri El-Saied (Applied Sciences, 2022)
Protecting tissues from excessive inflammation by glucocorticoids results in an effective blockade of inflammation; however, it does not instigate processes of inflammatory resolution or tissue repair. Moreover, glucocorticoids have side effects such as a susceptibility to infections. In otolaryngology—specifically, within the inner ear—surgical and non-surgical pathologies include cochlear implantation, stapes surgery, perilymph fistulas and Meniere’s disease. For these, steroids are indicated in order to prevent excessive inflammation that might lead to hearing and vestibular failure. Unless tissue homeostasis is restored, the compromised tissue is at risk of a functional loss. α1-Antitrypsin (AAT) is a circulating inflammation-modulating molecule that rises during the molecular signs of a tissue injury; it manipulates inflammation towards an inflammatory resolution and advances tissue repair. Lifelong infusions of AAT are currently indicated for genetic AAT deficiencies and are safe. In the present review, we discuss the advantages and downfalls of glucocorticoid treatments across several surgical inner ear injuries alongside evidence of the beneficial attributes of treatments with AAT. Collectively, the present knowledge places AAT treatments, wither independent or in combination with glucocorticoids, as adding focus on tissue repair in the context of unmet medical needs in otolaryngology.